RANCANG BANGUN APLIKASI UJIAN ONLINE REAL TIME DENGAN MENGGUNAKAN ARISTEKTUR MEAN - Rismanto, Ridwan; Arhandi, Putra Prima; Prasetyo, Arief (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
The development of information technology has developed rapidly into the world of education where more and more campuses and institutions use a variety of web based applications to simplify and accelerate the education services on campus or institution, one of which is the Department of Information Technology State Polytechnic of Malang to the field of web-based applications are frequently used applications is e-learning. One important part of e-learning applications that frequently used are online exams, where student can use the application to take online exam. However, online exam applications is not without drawbacks some weakness that often occurs is the application became slower and less responsive when accessed by many student. To overcome those problems in this research we develop an web based application that uses MEAN (MongoDB, Express Js, Angular Js, Js Node arcitecture).Based on our test with 100 to 150 client that connected simultaniously to our online exam application for one minutes the application have 3938 ms average of response time. Â Keywords Â : Online Examination, e-learning, MEAN